Elevated TyG-BMI significantly increases the 1-year stroke recurrence risk in patients with acute ischemic stroke and hypertension - Liu, Yan; Liu, Zhongzhong; Lu, Qingli; Liu, Pei; Zhang, Mi; Chang, Qiaoqiao; Liu, Tong; Peng, Linna; Rao, Lanping; Sun, Chao; Li, Guo; Cao, Shundao; et al. (Frontiers in Endocrinology, 2025)
ObjectivesTo investigate the association between triglyceride-glucose-body mass index (TyG-BMI) and the 1-year stroke recurrence risk in patients with acute ischemic stroke (AIS) and hypertension.MethodsIn this retrospective, multicenter cohort study, multivariable Cox proportional hazards models were constructed, and curve fitting and subgroup analyses were performed to evaluate the aforementioned association. TyG-BMI was analyzed as a continuous variable and in quartiles (Q1–Q4). Sex-specific stratified analyses were performed to explore potential effect modifications.ResultsAmong 1,620 enrolled patients (39.6% women; mean age 65.2 ± 11.5 years), elevated TyG-BMI was significantly associated with increased 1-year stroke recurrence risk after adjusting for potential confounding factors (hazard ratio [HR]=1.06, 95% confidence interval [CI]: 1.01–1.11, P = 0.032). This association was particularly prominent in women (HR = 1.18, 95%CI: 1.07–1.29, P<0.001). Women in the Q3 and Q4 TyG-BMI groups had significantly higher 1-year stroke recurrence risks (Q3: HR=8.81 95%CI: 2.22–34.97, P = 0.002; Q4: HR=5.79 95%CI: 1.49–22.56, P = 0.011) compared with those in the Q1 group. No significant association was observed in men (HR = 1.01, 95%CI: 0.94–1.08, P = 0.830). Segmented linear regression and curve fitting revealed a significant sex-specific nonlinear relationship between TyG-BMI and 1-year stroke recurrence risk. For women when TyG-BMI was below 221.97, each unit increase was associated with a more pronounced increase in the risk of 1-year stroke recurrence compared to patients above this threshold (adjusted HR = 1.04, 95% CI 1.01–1.07, P = 0.005).ConclusionElevated TyG-BMI is independently associated with a higher risk of 1-year stroke recurrence in patients with AIS and hypertension. A significant association was identified only in women, specifically among those with a TyG-BMI below 221.97, below which each unit increase in TyG-BMI was associated with a significantly greater risk of 1-year stroke recurrence compared to those above this threshold.